Decrease in the incidence of charcoal root rot in common bean (Phaseolus vulgaris L.) by Bacillus amyloliquefaciens B14, a strain with PGPR properties - Sabate, Daniela Constanza (2017)
The objective of this study was to isolate strains of the genus Bacillus from different productive soils of the province of Salta, Argentina, which have growth promoting properties in common bean (Phaseolus vulgaris L.) and have the ability to inhibit different phytopathogenic fungi, primarily Macrophomina phaseolina. Among the 105 strains of bacilli checked, Bacillus sp. B14 was selected for having the greatest in vitro inhibitory effect against Sclerotium rolfsii, Sclerotinia sclerotiurum, Rhizoctonia solani, Fusarium solani and Macrophomina phaseolina, recording fungal inhibition values that varied between 60 and 80%. In addition, B14 produced auxins in a concentration of 10.10 mg/ml, and qualitatively synthesizes siderophores. Based on 16S rRNA gene sequencing, the strain was characterized as B. amyloliquefaciens. Data from greenhouse experiments showed that the black common bean cv. Nag 12 seeds inoculated with B14, had increased germination of 10%, as well as an increase in root length of 2 cm and in shoot length of 6 cm compared with the non-inoculated control seeds. When the phytosanitary state of the B14 inoculated seeds was analyzed, no growth of bacteria, or phytopathogenic fungi and contaminants was observed, while in the non-inoculated seeds, bacteria was found in 46% of seeds, in addition to other phytopathogenic fungi. B. amyloliquefaciens B14 reduced the incidence of M. phaseolina by 62% in the inoculated black bean cv. Nag 12 seeds. Furthermore, using MALDI-MS it was determined that the bacteria synthesized different lipopeptides in the presence of M. phaseolina, such as surfactin, iturin, fengycin, kurstatin and polymyxin, leading us to conclude that they are the main responsible for the antagonistic effect observed and that the nature of lipopeptides synthesized by B14 is influenced by target fungal strain.